Analysis of Online Learning on Students' Morals in Diniyyah Education at SMPN 2 Tembelang - Sholihah, Fatikhatun Nikmatus; Razak, Raka Ansar (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Diniyah education is a branch of science that applies classical or modern teaching as well as an effort to instill Islam as part of the foundation of students' lives. The purpose of this study is to describe the impact of online learning on students' morale in the subject of early education at SMPN 2 Tembelang. In this study, the researcher used a qualitative descriptive research method. The data collection methods used are: 1. Observation, 2. Interview, 3. Documentation. Data analysis uses data reduction, presenting data and drawing research conclusions. The results of this study are: 1) Online learning has limitations in providing real practical experience, so teachers cannot immediately correct mistakes and improve students' understanding. The use of videos for practice is also limited and difficult to assess properly. Although the pandemic has worsened the learning situation, there is an increase in potential when learning is conducted face-to-face. 2) At the time of learning, not all students collect assignments in early education because of material difficulties such as writing Arabic pegon, interpreting Arabic, reading books, and nadloman. Children are still unfamiliar and need a lot of hands-on practice, which is difficult to do in online learning because it requires explanations and direct examples.